2020
DOI: 10.1371/journal.pone.0238107
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax after CT-guided transthoracic lung biopsy: A comparison between immediate and delayed occurrence

Abstract: Background In CT-guided transthoracic lung biopsy (CTLB), pneumothorax can occur as a late complication (delayed pneumothorax). The incidence, risk factors, and clinical significance of delayed pneumothorax are not well known. Objectives To compare the risk factors for immediate and delayed pneumothorax after CTLB and to know their clinical significance. Methods Images and medical records of 536 consecutive patients who underwent CTLB were reviewed. All biopsies were performed as inpatient procedures. Follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…According to previous studies, 8–10 lower lobe location is regarded as a risk factor for pneumothorax compared to the upper and middle lobe location, mainly due to greater respiratory motion of the lower lobe. However, investigators have reported delayed pneumothorax more frequently occurring in upper lobes, 11–13 which was not consistent with previous studies in which all cases of pneumothorax were included regardless of the onset. In general, lower lobe location with great movement may lead to the early appearance of pneumothorax, and upper lobe location with less movement may result in the late appearance of pneumothorax.…”
Section: Factors Influencing the Pneumothorax Formationmentioning
confidence: 65%
See 1 more Smart Citation
“…According to previous studies, 8–10 lower lobe location is regarded as a risk factor for pneumothorax compared to the upper and middle lobe location, mainly due to greater respiratory motion of the lower lobe. However, investigators have reported delayed pneumothorax more frequently occurring in upper lobes, 11–13 which was not consistent with previous studies in which all cases of pneumothorax were included regardless of the onset. In general, lower lobe location with great movement may lead to the early appearance of pneumothorax, and upper lobe location with less movement may result in the late appearance of pneumothorax.…”
Section: Factors Influencing the Pneumothorax Formationmentioning
confidence: 65%
“… 13 Delayed pneumothorax showed higher requirement of chest tube insertion compared to immediate pneumothorax, ranging from 7.1% to 29.6% of the overall rate of pneumothorax. 11 Therefore, the treatment of this condition is clinically significant.…”
Section: Management Of Delayed Pneumothoraxmentioning
confidence: 99%
“…15,17,26 Surprisingly, there was no relationship between pneumothorax and emphysema of the underlying lung, in contrast to reports. 11,13,15,27 The only explanation for this could be the limited number of patients with emphysema in this study, which may have obscured the expected increased risk of pneumothorax. An increased overall pulmonary hemorrhage was observed with underlying emphysema.…”
Section: Discussionmentioning
confidence: 88%
“… 13 In our case, pneumothorax, which actually existed, could not be detected by CXR and may have caused the diagnosis to be delayed, or as in some of the reported cases, a delayed pneumothorax occurred. 13 , 16 …”
Section: Discussionmentioning
confidence: 49%
“…1 t test, 2 Fischer's exact test, 3 Man-Whitney U test, 4 Pearson's chi square test, 5 Continuity-corrected chi-square test The rate of pneumothorax varied in previous studies from between 12-45% and 2-15% of cases required a chest tube replacement. 9,[13][14][15] In our study, a 22% rate of pneumothorax with a 5.7% rate of chest tube replacement was identified. In previous studies, factors increasing the risk of pneumothorax included a smaller lesion size, underlying emphysema, an increased depth of lesion, multiple pleural passes, and fissure punctures.…”
Section: Discussionmentioning
confidence: 58%